The impact of vocabulary selection ability on EFL students’ communication skills - I Ketut Wardana (Erudita: Journal of English Language Teaching, 2023)
Managing the flow of language in broader culture-based expressions in standardized communication belongs to one of crucial things to gain proficiency in English. Recent studies focus solely on the phenomenon of language proficiency, without considering the integrative elements of language proficiency as a learning achievement. Therefore, this study aims to investigate a causal-effect relationship between students’ ability to choose the right vocabulary and their communication skills. The researcher conducted an afterthought research design whose sole purpose was to accurately see the impact of one variable on another. In this study, 40 tenth grade vocational high school students in Badung, Bali, Indonesia participated using a targeted sampling technique. Data were collected by conducting two types of tests used to measure students' ability in distinguishing vocabulary use in listening activities and to check writing proficiency test. The data were analyzed with SPSS 25.0. The results showed that the ability to distinguish vocabulary statistically affected the clear flow of English communication, such as in building their conversation, lack of confidence, lack of variety, or improper politeness led to misunderstandings. Therefore, this study suggests that teachers use a teaching strategy to integrate all elements of communication for better language skills.